2012
DOI: 10.1007/s10544-012-9717-9
|View full text |Cite
|
Sign up to set email alerts
|

Hollow microneedles for intradermal injection fabricated by sacrificial micromolding and selective electrodeposition

Abstract: Limitations with standard intradermal injections have created a clinical need for an alternative, low-cost injection device. In this study, we designed a hollow metal microneedle for reliable intradermal injection and developed a high-throughput micromolding process to produce metal microneedles with complex geometries. To fabricate the microneedles, we laser-ablated a 70 μm × 70 μm square cavity near the tip of poly(lactic acid-co-glyoclic acid) (PLGA) microneedles. The master structure was a template for mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…This shrinking can be reduced to values of around 1-2 % by incorporating some additional outer pillars connected to the surface. These pillars act as support structures and absorb stress, as previous research has shown (Norman et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shrinking can be reduced to values of around 1-2 % by incorporating some additional outer pillars connected to the surface. These pillars act as support structures and absorb stress, as previous research has shown (Norman et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…for micromolding (Norman et al 2013), and they can be Fig. 4 Overview of the multiscale biomedical microsystem, with the outer structure obtained using the Heidelberg Laser Writer and with the textured channels obtained using the NanoScribe system …”
Section: Resultsmentioning
confidence: 99%
“…Typical master structures for micromolding are fabricated by micromachining or laser drilling of a bulk material which can be time consuming and ultimately limits the minimum feature size of the needle [1,9]. However after the master structure is complete, the micromolding process allows for fast fabrication of large numbers of microneedles.…”
Section: Cnt-su8 Compositementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Silicon has been used predominantly for fabrication of microneedles, however the fragility and the cost of the microfabrication process are major drawbacks for this material. [1][2][3][4] Injection molding has instead emerged as an alternative fabrication process offering advantages such as cost and robustness. 16,17 Microneedles can offer minimally invasive tools in the field of analytic a l science for example in order to achieve high-density chemical mapping thus to measure chemical heterogeneities in biological systems such as in tissues and organs.…”
Section: Introductionmentioning
confidence: 99%